Aboriginal pastoral properties, Arnhem Land Northern Territory. - Australia. Bureau of Agricultural Economics (Canberra, 1971)
Final report of investigations carried out in May 1970; terms of reference, general outline, major factors affecting budget estimates, budget assumptions & results (includes labour requirements)
Keywords: Agricultural colonies -- Northern Territory -- Case studies; Livestock -- Northern Territory -- Case studies; Cost effectiveness; Finance - Budgets; Economic sectors - Agriculture and horticulture - Pastoral industry; Arnhem Land (NT)